Evaluation of Operation IceBridge quick‐look snow depth estimates on sea ice. Issue 21 (6th November 2015) - King, Joshua; Howell, Stephen; Derksen, Chris; Rutter, Nick; Toose, Peter; Beckers, Justin F.; Haas, Christian; Kurtz, Nathan; Richter‐Menge, Jacqueline
Abstract: We evaluate Operation IceBridge (OIB) "quick‐look" snow depth on sea ice retrievals using in situ measurements taken over immobile first‐year ice (FYI) and multiyear ice (MYI) during March of 2014. Good agreement was found over undeformed FYI (−4.5 cm mean bias) with reduced agreement over deformed FYI (−6.6 cm mean bias). Over MYI, the mean bias was −5.7 cm, but 54% of retrievals were discarded by the OIB retrieval process as compared to only 10% over FYI. Footprint scale analysis revealed a root‐mean‐square error (RMSE) of 6.2 cm over undeformed FYI with RMSE of 10.5 cm and 17.5 cm in the more complex deformed FYI and MYI environments. Correlation analysis was used to demonstrate contrasting retrieval uncertainty associated with spatial aggregation and ice surface roughness. Key Points: OIB QL snow depth on sea ice retrieval performs well in level ice environments Deformed first‐year and multiyear ice are difficult retrieval environments for the OIB QL product Surface roughness contributes to diminished correlation between measured and retrieved snow depths